Effect of Synthetic Quadripolymer on Rheological and Filtration Properties of Bentonite-Free Drilling Fluid at High Temperature - Jiangfeng Wang; Mengting Chen; Xiaohui Li; Xuexuan Yin; Wenlong Zheng (Crystals, 2022)
High temperature would dramatically worsen rheological behaviors and increase filtration loss volumes of drilling fluids. Synthetic polymers with high temperature stability have attracted more and more attention. In this paper, a novel quadripolymer was synthesized using 2-acrylamido-2-methylpropanesulfonic acid (AMPS), acrylamide (AM), sodium styrene sulfonate (SSS), and dimethyl diallyl ammonium chloride (DMDAAC). Firstly, the molecular structure was studied by Fourier transform–infrared spectroscope (FT-IR) and nuclear magnetic resonance (1H-NMR) analysis. It was shown that the synthetic polymer contained all the designed functional groups. Moreover, the effect of temperature and the quadripolymer concentration on the rheological behavior and filtration loss of the bentonite-free drilling fluid were investigated. It was experimentally established that when the adding amount of the quadripolymer was 0.9 wt%, the prepared drilling fluid systems exhibited relatively stable viscosities, and the filtration losses could be controlled effectively after hot rolling aged within 180 °C. Further, it was confirmed that the bentonite-free drilling fluid containing the synthesized quadripolymer had good reservoir protection performance. In conclusion, the synthetic quadripolymer is a promising rheology modifier and a filtrate reducer for the development of the bentonite-free drilling fluid at high temperature.